Environment-friendly polishing pad and preparation method thereof
By using biomass-based polyurethane resin to prepare the polishing pad, the problem of environmental friendliness and high-efficiency polishing performance in the prior art is solved, and the effect of excellent polishing rate and stable physical properties is achieved in the semiconductor preparation process.
Patent Information
- Application Number
- CN202411130885.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-19
- Filing Date
- 2024-08-16
- Publication Date
- 2025-02-21
AI Technical Summary
It is difficult for existing polishing pads to balance environmental friendliness and efficient polishing performance in semiconductor preparation processes, and their physical properties fluctuate in terms of polishing rate and pad cutting rate.
The polishing pad is prepared using biomass-based polyurethane resin. By adjusting the composition and content of the raw materials of biomass, the biomass content in the polishing pad is controlled to ensure that it has the appropriate hardness, modulus, tensile strength and elongation in the CMP process. .
A polishing pad with excellent environmental friendliness is realized, which exhibits excellent polishing rate and pad cutting rate in the CMP process, while also having stable physical properties.
Smart Images

Figure CN119489398A_ABST
Abstract
Description
Technical Field
[0001] The present embodiment relates to a polishing pad for a chemical mechanical planarization process of a semiconductor device. Specifically, the present embodiment relates to an environmentally friendly biomass-based polishing pad and a preparation process thereof. Background Art
[0002] In the semiconductor manufacturing process, the chemical mechanical planarization (CMP) process refers to fixing a semiconductor substrate, such as a wafer, on a head and contacting it with the surface of a polishing pad mounted on a platen, and flattening irregularities on the surface of the semiconductor substrate through relative movement between the platen and the head.
[0003] In the CMP process, the polishing pad needs to have stable physical properties because it has a significant impact on the quality of the surface processing of the semiconductor substrate. In particular, since the polishing rate in the CMP process may fluctuate sensitively due to changes in the components contained in the polishing pad and its physical properties, it is necessary to optimize the components and physical properties of the polishing pad.
[0004] At the same time, with the emergence of environmental issues such as climate change in recent years, public opinion believes that companies should assume social responsibility through ESG management such as carbon neutrality to build a sustainable society. Therefore, companies are trying to manufacture various products by applying plant-derived biomass raw materials to replace petroleum-based raw materials.
[0005] In line with this trend, attempts are being made to apply biomass raw materials to polishing pads that were previously manufactured using petroleum-based raw materials to improve their environmental friendliness. In addition, even when these biomass raw materials are used, polishing pads with physical properties that enable the required polishing rate to be achieved in the CMP process must still be provided.
[0006] Prior art literature
[0007] Patent Literature
[0008] (Patent Document 1) Korean published patent application number 2018-0044771. Summary of the invention
[0009] Technical issues
[0010] The present embodiment aims to provide a polishing pad that is excellent in environmental friendliness and can achieve a polishing rate level required in a CMP process.
[0011] In addition, the present embodiment aims to provide a preparation process capable of efficiently preparing the above-mentioned polishing pad.
[0012] Solution
[0013] According to one embodiment, a polishing pad is provided, comprising a polishing layer, wherein the polishing layer comprises a polyurethane resin, the polyurethane resin comprises a polyol and a polyisocyanate, and the polyol comprises a bio-based polymer polyol.
[0014] According to another embodiment, a process for preparing a polishing pad is provided, the process comprising: preparing a urethane prepolymer comprising a polyol and a polyisocyanate; and curing the urethane prepolymer to prepare a polishing layer comprising a polyurethane resin, wherein the polyol comprises a bio-based polymer polyol.
[0015] According to another embodiment, a polishing pad is provided, comprising a polishing layer, wherein the polishing layer comprises a polyurethane resin, wherein the polyurethane resin comprises a polyol component and a polyisocyanate component, and the polyol component comprises a bio-based polymer polyol and a bio-based monomer polyol.
[0016] According to another embodiment, a process for preparing a polishing pad is provided, the process comprising: preparing a bio-based urethane prepolymer using a polyurethane resin comprising a polyol component and a polyisocyanate component; and curing the bio-based urethane prepolymer to prepare a polishing layer, wherein the polyol component comprises a bio-based polymer polyol and a bio-based monomer polyol.
[0017] Beneficial Effects of the Invention
[0018] The polishing pad according to one embodiment is prepared using a composition containing a biomass raw material, wherein the content of biomass in the polishing pad is controlled within a certain range by adjusting the composition and content of the biomass raw material. Therefore, the polishing pad has excellent environmental friendliness, and has physical properties such as hardness, modulus, tensile strength and elongation suitable for CMP process, and has excellent polishing rate and pad cutting rate.
[0019] In addition, a polishing pad according to an embodiment includes a polishing layer including a polyurethane resin, wherein the polyurethane resin includes a polyol component and a polyisocyanate component, and the polyol component includes a bio-based polymer polyol and a bio-based monomer polyol. Due to its excellent environmental friendliness and physical properties required for a CMP process, the polishing pad can be used to manufacture a semiconductor substrate and exhibits excellent performance.
[0020] Therefore, when a CMP process is performed using the polishing pad according to an embodiment, a semiconductor substrate such as a wafer having excellent surface processing quality can be provided while achieving a high polishing rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The polishing layer according to one embodiment is shown 13 C-NMR spectrum.
[0022] Figure 2 A polishing layer according to another embodiment is shown. 13 C-NMR spectrum.
[0023] Figure 3 is a cross-sectional view of a polishing pad according to an embodiment.
[0024] Figure 4 A process for preparing a semiconductor device using a polishing pad according to an embodiment is described.
[0025] [Explanation of Reference Numerals]
[0026] 1: Peak 1
[0027] 2: Peak 2
[0028] 3: Peak 3
[0029] 4: Peak 4
[0030] 5: Peak 5
[0031] 10: Polishing layer
[0032] 20: Adhesive layer
[0033] 30: Support layer
[0034] 100: Polishing pad
[0035] 200: Pressure plate
[0036] 300: Regulator
[0037] 400: Polishing slurry
[0038] 510: Polishing head
[0039] 520: Carrier
[0040] 600: Semiconductor substrate (wafer). DETAILED DESCRIPTION
[0041] In the following description of the embodiment, in order to avoid making the subject matter of the embodiment unclear, detailed description of known functions and configurations will be omitted. In addition, for the convenience of description, the size of each element in the drawings may be exaggerated or omitted, and they may be different from the actual size.
[0042] In this specification, when describing that a component is formed above / below another component, or connected or coupled to another component, it includes the case where these components are formed, connected or coupled directly or indirectly through another component. In addition, it should be understood that the terminology standard of the upper and lower of each component may vary depending on the direction of the object of observation.
[0043] In the present specification, the terms referring to various components are used to distinguish them from each other, and are not intended to limit the scope of the embodiments. In addition, in the present specification, unless the context clearly stipulates otherwise, a singular expression should be construed as including the plural.
[0044] In the present specification, the terms first, second, etc. are used to describe various components, but these components should not be limited by these terms. The purpose of using these terms is to distinguish one element from another element.
[0045] In the present specification, when it is mentioned that a part “comprises” a certain element, unless otherwise specified, it should be understood that other elements may be included rather than excluded.
[0046] For convenience, the molecular weight of the compound or polymer described in this specification is expressed in molar mass units, but can be understood as a relative mass relative to carbon- 12. In addition, the molecular weight of the compound or polymer described in this specification can be interpreted as a number average molecular weight or a weight average molecular weight, such as a number average molecular weight.
[0047] All numerical ranges related to physical properties, dimensions, etc. of components used in this specification are to be understood as being modified by the word "about" unless otherwise indicated.
[0048] In the numerical ranges of dimensions, physical properties, etc. of components described in this specification, when a numerical range limited to an upper limit and a numerical range limited to a lower limit are separately exemplified, it should be understood that the numerical range combining these upper and lower limits is also included in the exemplary range of the present invention.
[0049] In this specification, a "bio-based" component refers to a component that uses biomass from plants as all or part of the raw material, rather than using fossil fuel-based materials such as petroleum. Specifically, it is a component containing carbon-14 ( 14 C), carbon-14 is a radioactive carbon isotope that is only found in bio-based materials and not in fossil fuel-based materials such as petroleum.
[0050] For example, "bio-based polyols" refer to polyols obtained using biomass from plants as all or part of the raw material. 14 C), can be compared with those without radiocarbon ( 14 C) are distinguished from polyols obtained from fossil fuel-based materials.
[0051] Biomass is a broad concept that covers materials of biological origin, such as animal and plant resources, plant resources such as trees, flowers, corn, sugar cane, grass, whale oil, algae, etc.; or organic waste resources such as livestock and poultry manure, food waste, sawdust, etc. Biomass may contain radiocarbon ( 14 C).
[0052] Polishing pad
[0053] A polishing pad according to an embodiment includes a polishing layer, wherein the polishing layer includes a polyurethane resin, the polyurethane resin includes a polyol and a polyisocyanate, and the polyol includes a bio-based polymer polyol.
[0054] According to another embodiment, a polishing pad is provided, comprising a polishing layer, wherein the polishing layer comprises a polyurethane resin, wherein the polyurethane resin comprises a polyol component and a polyisocyanate component, and the polyol component comprises a bio-based polymer polyol and a bio-based monomer polyol.
[0055] The polyurethane resin of the polishing layer can be prepared from an urethane prepolymer comprising polyol and polyisocyanate. More specifically, it can be prepared from a composition comprising the urethane prepolymer, a curing agent and a foaming agent.
[0056] Bio-based polymer polyols
[0057] According to one embodiment, the polyurethane resin comprises a polyol component, and the polyol component comprises a bio-based polymer polyol.
[0058] The bio-based polymer polyol is a polymer polyol derived from biomass and contains the radioactive carbon isotope carbon-14 ( 14 C). It has 2 or more hydroxyl (OH) groups and may have 2 or more, 5 or more, or 10 or more repeating units.
[0059] Specifically, the bio-based polymer polyol may include at least one selected from the following group: a bio-based polyether polyol, a bio-based polyester polyol, a bio-based polycarbonate polyol, and a bio-based polycaprolactam polyol.
[0060] When the molecular weight, hydroxyl value (OH value) and number of functional groups of the bio-based polymer polyol are adjusted to a specific range, it is more advantageous to provide a polishing pad having excellent flexibility, elastic recovery, permanent strain, weather resistance and hydrolysis resistance.
[0061] In addition, controlling the properties of bio-based polymer polyols, such as weight-average molecular weight, hydroxyl value (OH value) and number of functional groups, is crucial to enhancing the flexibility, elastic recovery, permanent strain, weather resistance and hydrolysis resistance of polishing pads.
[0062] For example, the molecular weight of the bio-based polymer polyol can be 300 g / mole or greater, 400 g / mole or greater, 450 g / mole or greater, 500 g / mole or greater, 600 g / mole or greater, 700 g / mole or greater, or 800 g / mole or greater, and 5000 g / mole or less, 4000 g / mole or less, 3000 g / mole or less, 2700 g / mole or less, 2300 g / mole or less, 1800 g / mole or less, 1500 g / mole or less, or 1200 g / mole or less.
[0063] As a specific example, the molecular weight of the bio-based polymer polyol may be 400 g / mole to 3000 g / mole.
[0064] More specifically, the molecular weight of the bio-based polymer polyol can be 450 g / mole to 2700 g / mole, 500 g / mole to 2300 g / mole, 600 g / mole to 1800 g / mole, 700 g / mole to 1500 g / mole, or 800 g / mole to 1200 g / mole.
[0065] In addition, the hydroxyl value (OH value) of the bio-based polymer polyol can be, for example, 35 mg KOH / g or more, 45 mg KOH / g or more, 60 mg KOH / g or more, 70 mg KOH / g or more, 80 mg KOH / g or more, or 90 mg KOH / g or more, and 250 mg KOH / g or less, 230 mg KOH / g or less, 200 mg KOH / g or less, 180 mg KOH / g or less, 150 mg KOH / g or less, or 130 mg KOH / g or less.
[0066] In a specific embodiment, the hydroxyl value (OH value) of the bio-based polymer polyol may be 35 mg KOH / g to 250 mg KOH / g.
[0067] More specifically, the hydroxyl value (OH value) of the bio-based polymer polyol can be 45 mg KOH / g to 230 mg KOH / g, 60 mg KOH / g to 200 mg KOH / g, 70 mg KOH / g to 180 mg KOH / g, 80 mg KOH / g to 150 mg KOH / g, 90 mg KOH / g to 130 mg KOH / g, or 100 mg KOH / g to 125 mg KOH / g.
[0068] The number of functional groups of the bio-based polymer polyol can be 2 or more, or 3 or more, and can be 10 or less, 5 or less, 4 or less, or 3 or less. More specifically, the number of functional groups of the bio-based polymer polyol can be 2 to 4.
[0069] Examples of commercially available bio-based polymer polyols include EcoTRION H2000 and EcoTRION H1000 from SK Chemical; BI-550 and B-1184 from SK Pucore; Sovermol 1102, Sovermol 1005, Sovermol 805, and Sovermol 815 from BASF; BP-04 and BP-05 from Noroo; Priplast 2033 and Priplast 1838 from Croda; Velvetol H500, Velvetol H1000, Velvetol H2000, and Velvetol H2700 from Allessa; and combinations thereof.
[0070] The biomass content in the bio-based polymer polyol can be, for example, 10 wt % or more, 20 wt % or more, 30 wt % or more, 50 wt % or more, 60 wt % or more, 70 wt % or more, or 80 wt % or more, and can be 100 wt % or less, 90 wt % or less, or 85 wt % or less.
[0071] More specifically, based on the total weight of the bio-based polymer polyol, the biomass content may be 20 wt % to 100 wt %, 40 wt % to 100 wt %, 50 wt % to 100 wt %, 60 wt % to 100 wt %, 70 wt % to 100 wt %, or 80 wt % to 100 wt %. When the biomass content of the bio-based polymer polyol is within the above range, a polishing pad having excellent environmental friendliness and physical properties required for a CMP process can be provided.
[0072] The biomass content can be measured according to ASTM D 6866. ASTM D 6866 is a standard analytical method for determining the biomass content of solid, liquid or gas samples using radiometric dating or accelerator mass spectrometry (AMS).
[0073] Radioactive dating may include the following steps. Specifically, a sample (test specimen) that has been pretreated (such as removing foreign matter) is placed in a special vacuum device and burned to produce carbon dioxide. The molten lithium is then mixed to prepare lithium carbide, which reacts with water to produce acetylene gas after cooling. Next, the acetylene gas is purified and converted into benzene through an aluminosilicate catalyst. The benzene, which is 92% carbon, is then mixed with a scintillation chemical material and the radioactivity is measured for about 2 days using a liquid scintillation counter.
[0074] The accelerator mass spectrometry method may include the following steps. Specifically, a sample (test specimen) that has been pre-treated (e.g., to remove foreign matter) is burned to generate purified carbon dioxide, which is then reacted with hydrogen in a dedicated glass vacuum chamber to generate graphite. The graphite composed of 100% carbon is then placed in an accelerator mass spectrometer and the radioactivity is measured for about 30 minutes.
[0075] Bio-based Monomer Polyols
[0076] According to one embodiment, the polyurethane resin comprises a polyol component comprising a bio-based monomer polyol.
[0077] Specifically, the polyurethane resin may further comprise at least one bio-based monomer polyol. More specifically, the polyurethane resin may be prepared from a composition comprising at least one bio-based monomer polyol.
[0078] Thus, the polyurethane resin may comprise repeating units derived from a bio-based monomer polyol, as well as repeating units derived from a bio-based polymer polyol.
[0079] The bio-based monomer polyol is a monomer polyol derived from biomass that contains the radioactive carbon isotope carbon-14 ( 14 C) It has 2 or more hydroxyl (OH) groups.
[0080] Since bio-based monomer polyols are used together with bio-based polymer polyols, the cross-linking density of urethane prepolymers can be enhanced, thereby ensuring the hardness and durability required for the CMP process.
[0081] More specifically, the bio-based monomer polyol is most preferably bio-based 1,3-propylene glycol because it has a suitable weight average molecular weight and chain length, but is not limited thereto.
[0082] The bio-based monomer polyol may include at least one selected from the following group: bio-based ethylene glycol, bio-based diethylene glycol, bio-based 1,2-propylene glycol, bio-based 1,3-propylene glycol, bio-based 2-methyl-1,3-propanediol, bio-based 1,3-butanediol, bio-based 1,4-butanediol, bio-based 2,3-butanediol, bio-based 1,5-pentanediol, bio-based 1,9-nonanediol, bio-based 1,10-decanediol and bio-based isosorbide.
[0083] More specifically, the bio-based monomer polyol may include at least one selected from the following group: bio-based 1,3-propylene glycol, bio-based 1,3-butanediol, bio-based 1,4-butanediol, bio-based 2,3-butanediol, bio-based 1,5-pentanediol, bio-based 1,9-nonanediol, bio-based 1,10-decanediol and bio-based isosorbide.
[0084] In addition, the weight average molecular weight of the bio-based monomer polyol can be 50 g / mol to 200 g / mol. For example, the molecular weight of the bio-based monomer polyol can be 55 g / mol to 180 g / mol, 60 g / mol to 150 g / mol, 65 g / mol to 130 g / mol, 70 g / mol to 100 g / mol, or 75 g / mol to 90 g / mol. When the molecular weight of the bio-based monomer polyol is within the above range, a polishing pad with excellent hardness and durability can be provided.
[0085] The biomass content of the bio-based monomer polyol may be 50 wt % or more, 80 wt % or more, 90 wt % or more, 80 wt % to 100 wt % or 85 wt % to 100 wt %, more specifically 100 wt %, based on the total weight of the bio-based monomer polyol.
[0086] When the biomass content of the bio-based monomer polyol is within the above range, it may be more advantageous to provide a polishing pad having excellent environmental friendliness and physical properties required for a CMP process.
[0087] In addition, the weight ratio of the bio-based polymer polyol to the bio-based monomer polyol may be 5 to 20: 0.01 to 2. For example, the weight ratio of the bio-based polymer polyol to the bio-based monomer polyol may be 5 to 20: 0.02 to 2, 5 to 18: 0.05 to 2, 5 to 15: 0.1 to 2, 8 to 20: 0.2 to 2, or 8 to 15: 0.5 to 1.5.
[0088] Additional polyols
[0089] The polyol contained in the polyurethane resin constituting the polishing layer may further contain a petroleum-based polyol in addition to the bio-based polyol.
[0090] Specifically, the polyol may further include at least one selected from the following group: a petroleum-based polymer polyol and a petroleum-based monomer polyol.
[0091] The petroleum-based polymer polyol may include at least one selected from the following group: common polyether polyol, polyester polyol, polycarbonate polyol, and polycaprolactam polyol.
[0092] In addition, the petroleum-based monomer polyol may contain at least one selected from the following group: common ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, n-butanol, isobutanol, 1,5-pentanediol, 1,6-hexanediol, 2-octanol, 1,9-nonanediol and 1,10-decanediol.
[0093] When the polyol in the polyurethane resin contains both the bio-based polyol (a) and the petroleum-based polyol (b), their mixing ratio (a:b) can be a molar ratio of 1:0.65 to 1:3, a molar ratio of 1:0.65 to 1:1.5, a molar ratio of 1:0.65 to 1:1.25, a molar ratio of 1:0.65 to 1:0.92, a molar ratio of 1:0.68 to 1:0.90, a molar ratio of 1:0.72 to 1:0.88, a molar ratio of 1:0.75 to 1:0.86, or a molar ratio of 1:0.80 to 1:0.85.
[0094] Within the above-mentioned mixing ratio range, it is more advantageous to provide a polishing pad having excellent environmental friendliness and physical properties required for the CMP process.
[0095] Polyisocyanate
[0096] According to one embodiment, the polyurethane resin may include polyisocyanate.
[0097] Specifically, the polyisocyanate contained in the polyurethane resin constituting the polishing layer may be a common polyisocyanate, for example, a petroleum-based polyisocyanate, but is not limited thereto.
[0098] Specifically, the polyisocyanate may include at least one selected from the following group: aromatic diisocyanate, aliphatic diisocyanate and cycloaliphatic diisocyanate. More specifically, the polyisocyanate may include at least one selected from the following group: aromatic diisocyanate and cycloaliphatic diisocyanate.
[0099] For example, the polyisocyanate may include at least one selected from the following group: toluene diisocyanate (TDI), naphthalene-1,5-diisocyanate, p-phenylene diisocyanate, dimethylbiphenyl diisocyanate, 4,4-diphenylmethane diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate (H12MDI) and isophorone diisocyanate.
[0100] Preferably, the polyisocyanate may include toluene diisocyanate (TDI) and 4,4'-dicyclohexylmethane diisocyanate (H12MDI). When the above-exemplified isocyanates are used, the formed hard segments may be more conducive to providing a polishing pad having a desired hardness level.
[0101] When toluene diisocyanate (TDI) (x) and 4,4'-dicyclohexylmethane diisocyanate (H12MDI) (y) are mixed, the mixing ratio (x:y) thereof is not particularly limited, but may specifically be a weight ratio of 3:1 to 20:1, a weight ratio of 5:1 to 18:1, a weight ratio of 7:1 to 16:1, or a weight ratio of 8:1 to 13:1.
[0102] Curing agent and foaming agent
[0103] According to one embodiment, the polyurethane resin constituting the polishing layer may further include a curing agent and a foaming agent.
[0104] The curing agent may include a compound that undergoes a curing reaction with the urethane prepolymer used to prepare the polyurethane resin.
[0105] Specifically, the curing agent may include at least one selected from the following group: aromatic amines, aliphatic amines, aromatic alcohols, and aliphatic alcohols.
[0106] For example, the curing agent may include at least one selected from the following group: 4,4'-methylenebis(2-chloroaniline), diethyltoluenediamine, diaminodiphenylmethane, dimethylthio-toluenediamine, propylene glycol bis(p-aminobenzoate), diaminodiphenyl sulfone, m-xylylenediamine, isophoronediamine, ethylenediamine, diethylenetriamine, triethylenetetramine, polypropylenediamine, polypropylenetriamine, and bis(4-amino-3-chlorophenyl)methane.
[0107] The foaming agent is used to form a pore structure in the polishing layer, and may include at least one selected from the following group: a solid-phase foaming agent, a liquid-phase foaming agent, and a gas-phase foaming agent (eg, inert gases such as nitrogen, argon, and helium).
[0108] Specifically, the foaming agent can be a solid phase foaming agent containing expandable particles. The expandable particles are particles having the property of being expandable by heat or pressure. The size in the final polishing layer can be determined by the heat or pressure applied during the preparation of the polishing layer. More specifically, the expandable particles can include expanded particles, unexpanded particles or a combination thereof.
[0109] The heat-expandable particles are particles that have been heat-expanded in advance, and the heat-expandable particles are particles whose final size is determined by heat or pressure applied during the process of preparing the polishing layer.
[0110] The expandable particles may include a resin shell; and an expansion inducing component encapsulated within the shell.
[0111] The resin shell may include a thermoplastic resin. Specifically, the thermoplastic resin may be at least one selected from the following group: a vinylidene chloride-based copolymer, an acrylonitrile-based copolymer, a methacrylonitrile-based copolymer, and an acrylic acid-based copolymer.
[0112] The expansion inducing component may include at least one selected from the following group: a hydrocarbon compound, a chlorofluoro compound, and a tetraalkylsilane compound.
[0113] Specifically, the hydrocarbon compound may include at least one selected from the following group: ethane, ethylene, propane, propylene, n-butane, isobutane, n-butene, isobutene, n-pentane, isopentane, neopentane, n-hexane, heptane and petroleum ether.
[0114] The chlorofluorine compound may include at least one selected from the following group: trichlorofluoromethane (CCl3F), dichlorodifluoromethane (CCl2F2), chlorotrifluoromethane (CClF3) and dichlorotetrafluoroethane (CClF2-CClF2).
[0115] The tetraalkylsilane compound may include at least one selected from the group consisting of tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, and trimethyl-n-propylsilane.
[0116] In addition, the solid-phase foaming agent may have an average particle size of 5 μm to 200 μm, specifically 10 μm to 100 μm, 15 μm to 70 μm, or 20 μm to 45 μm. Wherein, when the solid-phase foaming agent includes heat-expandable particles as expandable particles, the average particle size may refer to the average particle size of the heat-expandable particles themselves. In addition, when the solid-phase foaming agent includes unexpanded particles as expandable particles, the average particle size may refer to the average particle size after the particles are expanded by heat or pressure.
[0117] Characteristics of polishing layer
[0118] The thickness of the polishing layer may be 0.5 mm to 5 mm. For example, the thickness of the polishing layer may be 0.8 mm to 4.0 mm, 1.0 mm to 3.0 mm, 1.5 mm to 2.5 mm, 1.7 mm to 2.3 mm, or 2.0 mm to 2.2 mm. When the thickness of the polishing layer is within the above range, the basic physical properties as a polishing pad can be fully guaranteed while minimizing the size change of the micropores between the upper and lower parts.
[0119] In addition, the hardness of the polishing layer may be 45 Shore D or more. For example, the hardness of the polishing layer may be 46 Shore D or more, 50 Shore D or more, 53 Shore D or more, or 56 Shore D or more, and may be 80 Shore D or less, 70 Shore D or less, 68 Shore D or less, 65 Shore D or less, or 60 Shore D or less.
[0120] As a specific example, the hardness of the polishing layer can be 45Shore D to 80Shore D, 45Shore D to 70Shore D, 46Shore D to 60Shore D, 50Shore D to 68Shore D, 53Shore D to 66Shore D, 53Shore D to 65Shore D, 55Shore D to 64Shore D, 56Shore D to 60Shore D or 56Shore D to 62Shore D.
[0121] The tensile strength of the polishing layer can be 5N / mm 2 or higher, 10N / mm 2 or higher, 15N / mm 2 or higher or 17N / mm 2 or higher, and can be 30N / mm 2 or lower, 28N / mm 2 or lower, 27N / mm 2 or lower, 26N / mm 2 or lower, 25N / mm 2 or lower, 23N / mm 2 or lower or 20N / mm 2 or lower.
[0122] As a specific example, the tensile strength of the polishing layer can be 5N / mm 2 Up to 30N / mm 2 , 10N / mm 2 Up to 25N / mm 2 , 12N / mm 2 Up to 27N / mm 2 , 15N / mm 2 Up to 25N / mm 2 , 15N / mm 2 Up to 23N / mm 2 , 20N / mm 2 Up to 25N / mm 2 , 16N / mm 2 Up to 24N / mm2 , 17N / mm 2 Up to 27N / mm 2 or 18N / mm 2 Up to 23N / mm 2 .
[0123] In addition, the elongation of the polishing layer may be 50% or more, 70% or more, 90% or more, 106% or more, or 120% or more, and may be 300% or less, 250% or less, 200% or less, or 150% or less. As a specific example, the elongation of the polishing layer may be 50% to 300%, 60% to 150%, 62% to 120%, 80% to 200%, 90% to 130%, 85% to 120%, 85% to 115%, 95% to 110%, or 98% to 105%. The elongation may be elongation at break.
[0124] According to one embodiment, the hardness of the polishing layer can be 45 Shore D to 70 Shore D, and the tensile strength can be 15 N / mm 2 Up to 27N / mm 2 , and the elongation can be 50% to 150%. Within the above-mentioned characteristic range of the polishing layer, the performances such as the polishing rate and the pad cutting rate in the CMP process can be further improved.
[0125] According to another embodiment, the hardness of the polishing layer can be 55 Shore D to 64 Shore D, and the tensile strength is 20 N / mm 2 Up to 25N / mm 2 , and the elongation is 85% to 115%. When the hardness, tensile strength and elongation of the polishing layer are adjusted to the above ranges, the CMP process can be stably performed and the polishing pad can be made lighter.
[0126] In particular, when all the properties of the polishing layer meet the above ranges, the performance in the CMP process, such as the polishing rate, the pad cutting rate, and the polishing speed, can be further improved. More specifically, when the hardness and the polishing rate of the polishing layer are controlled within the above ranges, an appropriate polishing rate can be ensured in the CMP process. When the elongation of the polishing layer is controlled within the above range, defects such as the polishing layer becoming brittle and thus breaking or leaving scratches on the surface of the object to be polished can be effectively prevented.
[0127] In addition, the average size of pores formed in the polishing layer is not particularly limited, but may be specifically 10 μm to 40 μm, 15 μm to 35 μm, 18 μm to 30 μm, or 20 μm to 25 μm.
[0128] When the thickness, hardness and average pore size of the polishing layer satisfy the above ranges, respectively, the CMP process can be performed more stably and the polishing pad can be made lighter.
[0129] The biomass content of the polishing layer can be 2 wt % to 70 wt %. Specifically, based on the total weight of the polishing layer, the biomass content of the polishing layer can be 3 wt % to 65 wt %, 5 wt % to 60 wt %, 6 wt % to 58 wt %, 7 wt % to 56 wt %, 8 wt % to 54 wt %, 20 wt % to 52 wt %, or 35 wt % to 50 wt %.
[0130] Meanwhile, the polishing layer is a hardened product composed of a compound having a specific chemical structure. The final polishing performance, such as the polishing rate and the degree of defects, can be determined according to the chemical structure of the compound and the bonding structure and bonding strength of the repeating units constituting the chemical structure. The compound contained in the polishing layer has various types of chemical bonding structures. When the polishing layer is treated under specific treatment conditions, the bonding may be broken or remain unchanged depending on the bonding strength of each bonding structure. Therefore, the carbon-13 nuclear magnetic resonance ( 13 The shape of the C-NMR spectrum may vary. Specifically, the carbon-13 nuclear magnetic resonance ( 13 The shape of the C-NMR) spectrum is not only related to the components and content of the polishing layer, but also to the various process conditions in the preparation of the polishing layer and the treatment conditions for obtaining the treatment composition.
[0131] In the polishing pad according to one embodiment, 1 g of the polishing layer was added to a potassium hydroxide (KOH) aqueous solution having a concentration of 0.3 M, reacted at 150° C. for 48 hours in a sealed container to obtain a test composition, and the test composition was measured. 13 C-NMR spectrum. At this time, it may have a first peak appearing between 28 ppm and 31 ppm, a second peak appearing between 31 ppm and 33 ppm, and a third peak appearing between 67 ppm and 71 ppm.
[0132] The polishing layer is composed of a compound having a chemical bonding structure corresponding to the spectral characteristics, thereby producing an effect of enhancing the polishing performance of the polishing pad.
[0133] The ratio (p1 / p2) of the area of the first peak (p1) to the area of the second peak (p2) can be, for example, 2 or more, 3 or more, 4 or more, or 4.4 or more, and 8 or less, 7 or less, 6 or less, or 5.7 or less. As a specific example, the ratio of the area of the first peak to the area of the second peak can be 4.4 to 5.7.
[0134] The ratio (p3 / p2) of the area of the third peak (p3) to the area of the second peak (p2) can be 6 or more, 7 or more, 8 or more, or 8.2 or more, and 11 or less, 10 or less, 9 or less, or 8.8 or less. In a specific example, the ratio of the area of the third peak to the area of the second peak can be 8.2 to 8.8.
[0135] In a specific embodiment, a ratio of the area of the first peak to the area of the second peak may be 4.4 to 5.7, and a ratio of the area of the third peak to the area of the second peak may be 8.2 to 8.8.
[0136] Within the above range of the peak area ratio, the polishing layer has appropriate hardness and elongation, thereby reducing defects while further improving the polishing rate.
[0137] In particular, the above 13 The C-NMR test conditions (i.e., adding 1 g of the polishing layer to a 0.3 M potassium hydroxide (KOH) aqueous solution and reacting at 150° C. for 48 hours in a sealed container to obtain a test composition) show a high correlation with the polishing performance of the final polishing pad compared to other test compositions prepared under different conditions. 13 C-NMR spectrum.
[0138] In the conditions of the polishing layer treatment, the pressure in the sealed container may be 3 bar or less. However, it is sufficient to use a sealed container, and there is no need to adjust the pressure to a specific condition.
[0139] In addition, the polishing layer 13 In addition to the first to third peaks, the C-NMR spectrum may have additional characteristic peaks.
[0140] In the polishing pad according to one embodiment, when measured under the same conditions 13 In C-NMR spectrum, the polishing pad may further include a fourth peak appearing between 33 ppm and 36 ppm and a fifth peak appearing between 61 ppm and 63 ppm.
[0141] The polishing layer is composed of a compound having a chemically bonded structure corresponding to the spectral characteristics of these additional peaks, thereby producing an effect of enhancing the polishing performance of the polishing pad.
[0142] The ratio (p4 / p5) of the area of the fourth peak (p4) to the area of the fifth peak (p5) may be 1 or more, 2 or more, or 2.1 or more, and 9 or less, 8 or less, 7 or less, or 6.4 or less.
[0143] In a specific embodiment, the ratio of the area of the fourth peak to the area of the fifth peak may be 2.1 to 6.4.
[0144] Within the above-mentioned peak area ratio range, the polishing layer has appropriate hardness and elongation, thereby further improving the polishing rate while reducing defects.
[0145] The test composition of the polishing layer 13 The shape of the C-NMR spectrum is determined by the combined results of multiple factors, such as the type and content of raw material monomers, process temperature and pressure conditions, and the type and content of additives such as curing agents and foaming agents in the process of preparing the polishing layer.
[0146] Additional component layers
[0147] Figure 3 is a cross-sectional view of a polishing pad according to an embodiment.
[0148] See also Figure 3 According to an embodiment, the polishing pad (100) may include a polishing layer (10) as a top pad layer, and may further include a support layer (30) as a subpad layer below the polishing layer (10). In addition, the polishing pad (100) may further include an adhesive layer (20) between the polishing layer (10) and the support layer (30).
[0149] The bonding layer is located between the polishing layer and the support layer, and is used to bond the polishing layer and the support layer to each other. In addition, the bonding layer can also prevent the polishing slurry supplied to the polishing layer from leaking into the support layer. The bonding layer can be formed using a hot melt adhesive composition.
[0150] The hot melt adhesive composition may include a common hot melt adhesive. Specifically, the hot melt adhesive may include at least one selected from the following group: a polyurethane resin, a polyester resin, an ethylene-vinyl acetate resin, a polyamide resin, and a polyolefin resin.
[0151] In addition, the thickness of the adhesive layer is not particularly limited, but may be, for example, 5 to 30 μm, 10 to 30 μm, 20 to 27 μm, or 23 to 25 μm. When the thickness of the adhesive layer satisfies the above range, a certain level of adhesive strength between the polishing layer and the support layer can be ensured.
[0152] The support layer is disposed below the polishing layer to stably support the polishing layer and absorb and / or disperse the impact applied to the polishing layer. The support layer may be prepared (formed) using nonwoven fabric, suede, or a porous pad.
[0153] The thickness of the support layer is not particularly limited, but may be specifically 0.5 mm to 4 mm, 0.6 mm to 3.5 mm, 0.8 mm to 3 mm, or 1 mm to 2 mm. In addition, the hardness of the support layer is not particularly limited, but may be, for example, 55 Asker C to 90 Asker C, 60 Asker C to 85 Asker C, 65 Asker C to 80 Asker C, or 70 Asker C to 75 Asker C. When the thickness and hardness of the support layer satisfy the above ranges, respectively, it can stably support the polishing layer, and the polishing pad can become lighter.
[0154] Polishing pad characteristics
[0155] The polishing pad according to an embodiment has excellent characteristics, such as polishing rate, in a CMP process.
[0156] For example, the polishing rate (removal rate) of a silicon oxide layer in a CMP process, more specifically, the polishing rate when a silicon oxide layer of a silicon wafer is polished using a polishing pad with a ceria slurry, may be or higher, or higher, or higher, or or higher, and can be or higher, or higher, or higher or or higher.
[0157] As a specific example, when the polishing pad is used to polish the silicon oxide layer of a silicon wafer with a cerium dioxide slurry, the polishing rate can be to to to to to or to
[0158]
[0159] Specifically, the polishing rate may be a polishing rate of a silicon wafer having a diameter of 300 mm on which silicon oxide is deposited. In addition, the polishing rate may be measured under a polishing load of 4.0 psi, while the polishing pad is rotated at a speed of 150 rpm, the calcined cerium oxide slurry is supplied to the polishing pad at a rate of 250 ml per minute, and the platen is rotated at a speed of 150 rpm for 60 seconds. The temperature conditions when measuring the polishing rate are not particularly limited, but may be, for example, room temperature conditions.
[0160] In addition, the pad cutting rate of the polishing pad may be 25 μm / hour or more, 30 μm / hour or more, 35 μm / hour or more, or 38 μm / hour or more, and may be 50 μm / hour or less, 45 μm / hour or less, or 42 μm / hour or less. As a specific example, the pad cutting rate of the polishing pad (i.e., the polishing layer) may be 25 μm / hour to 50 μm / hour, 30 μm / hour to 50 μm / hour, or 38 μm / hour to 48.5 μm / hour under the conditions of a regulated pressure of 6 lbf and a rotation speed of 100 rpm to 110 rpm.
[0161] In one embodiment, the polishing rate of the polishing pad in the CMP process is Can be to And the pad cutting rate (μm / hour) may be 38 μm / hour to 45 μm / hour.
[0162] In another specific embodiment, the polishing pad has a polishing rate in a CMP process of Can be to And the pad cutting rate (μm / hour) may be 30 μm / hour to 50 μm / hour.
[0163] Additionally, the polishing pad can have a compressibility of 0.3% to 1.8%, 0.4% to 1.6%, 0.5% to 1.5%, 0.6% to 1.4%, or 0.8% to 1.3%.
[0164] A polishing pad according to an embodiment can have excellent environmental friendliness because the polishing layer is prepared using a biomass-containing composition. In addition, according to an embodiment, a polymer component contained in a biomass-containing composition used for preparing a polishing layer in a polishing pad is adjusted, and more specifically, the composition and content of a bio-based polymer polyol and a bio-based monomer polyol in the polymer component are adjusted. Therefore, the polishing pad has physical properties required for a CMP process, and is excellent in polishing rate and pad cutting rate.
[0165] For example, based on the total weight of the polishing pad, the biomass content of the polishing pad according to an embodiment can be 1 wt % to 50 wt %. For example, based on the total weight of the polishing pad, the total biomass content in the polishing pad can be 2 wt % to 50 wt %, 3 wt % to 50 wt %, 4 wt % to 50 wt %, 5 wt % to 50 wt %, 6 wt % to 50 wt %, 7 wt % to 50 wt %, 8 wt % to 50 wt %, 2 wt % to 45 wt %, 3 wt % to 42 wt %, 4 wt % to 38 wt %, 4.5 wt % to 36 wt %, 5 wt % to 34 wt %, 8 wt % to 32 wt %, 15 wt % to 33 wt %, or 25 wt % to 32 wt %.
[0166] Process for preparing polishing pad
[0167] According to another embodiment, a process for preparing a polishing pad is provided, the process comprising: preparing a urethane prepolymer comprising a polyol and a polyisocyanate; and curing the urethane prepolymer to prepare a polishing layer comprising a polyurethane resin, wherein the polyol comprises a bio-based polymer polyol.
[0168] According to another embodiment, a process for preparing a polishing pad is provided, the process comprising: preparing a bio-based urethane prepolymer using a polyurethane resin comprising a polyol component and a polyisocyanate component; and curing the bio-based urethane prepolymer to prepare a polishing layer, wherein the polyol component comprises a bio-based polymer polyol and a bio-based monomer polyol.
[0169] Thus, the polishing pad may be provided with a polishing layer formed by curing a urethane prepolymer comprising a bio-based polymer polyol and a bio-based monomer polyol.
[0170] First, a urethane prepolymer comprising a polyol component and a polyisocyanate component is prepared. Specifically, a composition of a polyol component comprising a bio-based polymer polyol and a bio-based monomer polyol and a polyisocyanate can be fed into a reactor, and a prepolymerization reaction is performed to prepare the urethane prepolymer. The reaction conditions are not particularly limited, but the reaction temperature can be 70° C. to 90° C., or 75° C. to 85° C., and the reaction time can be 1 hour to 4 hours or 2 hours to 3 hours.
[0171] Meanwhile, the descriptions of the polyol and the isocyanate are the same as those described above with respect to the polishing pad.
[0172] In addition, in the reaction of the polyol component (z) and the polyisocyanate component (w), the reaction ratio (z:w) thereof is not particularly limited, but in consideration of the overall physical properties of the polishing layer, the weight ratio thereof may be 1:2 to 14, 1:3 to 12, 1:4 to 10, or 1:5 to 8.
[0173] The biomass content of the biomass-containing urethane prepolymer obtained by the reaction of the polyol component and the polyisocyanate can be 4 wt % to 80 wt %. For example, based on the total weight of the biomass-containing urethane prepolymer, the biomass content of the biomass-containing urethane prepolymer can be 4 wt % to 78 wt %, 7 wt % to 76 wt %, 8 wt % to 74 wt %, 9 wt % to 72 wt %, 10 wt % to 69 wt %, 25 wt % to 67 wt % or 45 wt % to 65 wt %.
[0174] The weight average molecular weight of the biomass-containing urethane prepolymer can be 500 g / mole to 1500 g / mole. For example, the weight average molecular weight of the biomass-containing urethane prepolymer can be 600 g / mole to 1400 g / mole, 700 g / mole to 1300 g / mole, or 800 g / mole to 1200 g / mole.
[0175] In addition, the terminal NCO content (NCO%) of the biomass-containing urethane prepolymer may be 6 wt % to 14 wt %. For example, the terminal NCO content (NCO%) of the biomass-containing urethane prepolymer may be 6.5 wt % to 13 wt %, 7 wt % to 12 wt %, 7.5 wt % to 11 wt %, or 8 wt % to 10 wt %. When the weight average molecular weight and NCO% of the biomass-containing urethane prepolymer satisfy the above ranges, respectively, a polishing pad having an excellent polishing rate in a CMP process may be provided.
[0176] Subsequently, the biomass-containing urethane prepolymer can be cured to prepare a polishing layer. Specifically, the bio-based urethane prepolymer can be cured to prepare a polishing layer comprising a polyurethane resin.
[0177] More specifically, the biomass-containing urethane prepolymer may be mixed with a curing agent, a foaming agent, a surfactant, a reaction rate controller, etc., and then cast to obtain a molded body, which is cut to prepare a polishing layer.
[0178] To this end, the urethane prepolymer, curing agent, foaming agent, etc. can be filled into respective injection lines for mixing to prepare the polyurethane resin. The mixing can be carried out at 1000 rpm to 10000 rpm, 250 0 The blowing agent may be mixed with the biomass-containing urethane prepolymer through an injection line separated from the injection line of the biomass-containing urethane prepolymer, or may be mixed with the biomass-containing urethane prepolymer in advance before the biomass-containing urethane prepolymer is filled into the injection line.
[0179] The detailed information of the curing agent is as described above. With respect to 100 parts by weight of the urethane prepolymer, the content of the curing agent can be 15 parts by weight to 55 parts by weight, 20 parts by weight to 50 parts by weight, 25 parts by weight to 45 parts by weight, or 30 parts by weight to 40 parts by weight. When the content of the curing agent meets the above range, it is more conducive to achieving a polishing pad with excellent physical properties.
[0180] The reaction ratio of the urethane prepolymer to the curing agent (curing reaction ratio) is not particularly limited, but may be, for example, an equivalent ratio of 1:0.5 to 1.3, an equivalent ratio of 1:0.6 to 1.2, an equivalent ratio of 1:0.7 to 1.1, or an equivalent ratio of 1:0.8 to 1. When the curing reaction is performed according to the above reaction ratio, the curing reaction is optimized, thereby providing a polishing pad having physical properties (hardness and modulus) required for a CMP process.
[0181] The foaming agent may be, for example, a solid-phase foaming agent. The content of the solid-phase foaming agent may be 0.5 to 10 parts by weight, specifically 0.7 to 8 parts by weight, 0.9 to 6 parts by weight, or 1 to 5 parts by weight, relative to 100 parts by weight of the biomass-containing urethane prepolymer. When the content of the solid-phase foaming agent satisfies the above range, it is more conducive to achieving a polishing pad with excellent physical properties.
[0182] The surfactant is not particularly limited, but may specifically be a silicon-based surfactant.
[0183] The reaction rate controller is not particularly limited, but may specifically include at least one selected from the following group: triethylenediamine, dimethylethanolamine, tetramethylbutylenediamine, 2-methyltriethylenediamine, dimethylcyclohexylamine, triethylamine, triisopropanolamine, 1,4-diazabicyclo[2,2,2]octane, bis(2-methylaminoethyl)ether, trimethylaminoethylethanolamine, N,N,N,N,N"-pentamethyldiethyldimethylethylamine, dimethylaminopropylamine, benzyldimethylamine, N-ethylmorpholine, N,N-dimethylaminoethylmorpholine, N,N-dimethylcyclohexylamine, 2-methyl-2-azanorbornane, dibutyltin dilaurate, stannous octoate, dibutyltin diacetate, dibutyltin diacetate, dibutyltin diacetate, dibutyltin di-2-ethylhexanoate, and dibutyltin dithiol.
[0184] The step of preparing the polishing layer may include injecting a composition mixed with a urethane prepolymer, a curing agent, and a foaming agent into a mold and performing a curing reaction. The curing reaction conditions are not particularly limited, but the curing reaction temperature may be 60° C. to 130° C. or 75° C. to 110° C., and the mold pressure may be 50 kg / m 2 Up to 260kg / m 2 or 80kg / m 2 Up to 180kg / m2 .
[0185] According to an embodiment, the process for preparing a polishing pad may further include preparing an adhesive layer and a support layer after preparing the polishing layer. In addition, a step of cutting the surface of the polishing layer, a step of processing grooves on the surface of the polishing layer, a step of inspecting the polishing pad, and a step of packaging the polishing pad may be further performed. A typical method for preparing a polishing pad may be used in these steps.
[0186] Chemical Mechanical Polishing (CMP)
[0187] A semiconductor device can be manufactured by performing chemical mechanical polishing using the polishing pad according to an embodiment.
[0188] A process for preparing a semiconductor device according to an embodiment includes polishing a surface of a semiconductor substrate using a polishing pad. Specifically, the process for preparing a semiconductor device may include providing a polishing pad according to an embodiment; and while a polishing surface of the polishing layer and a surface of the semiconductor substrate are in contact with each other, they are relatively rotated to polish the surface of the semiconductor substrate.
[0189] Figure 4 A process for preparing a semiconductor device using a polishing pad according to an embodiment is described. Figure 4 , once the polishing pad (100) according to an embodiment is fixed to the pressing plate (200), the semiconductor substrate (600) as the polishing object is placed on the polishing pad (100). In this case, the surface of the semiconductor substrate (600) to be polished is directly contacted with the polishing surface of the polishing pad (100). The polishing slurry (400) can be sprayed onto the polishing pad through a nozzle for polishing. Thereafter, the semiconductor substrate (600) and the polishing pad (100) are relatively rotated so as to polish the surface of the semiconductor substrate (600). In this case, the rotation direction of the semiconductor substrate (600) and the rotation direction of the polishing pad (100) can be the same direction or opposite directions. The semiconductor substrate (600) mounted on the polishing head (510) is pressed on the polishing surface of the polishing pad (100) with a predetermined load, contacts therewith, and then its surface can be polished. In addition, in order to keep the polishing surface of the polishing pad (100) in a state suitable for polishing, the process for preparing a semiconductor device may further include using a conditioner (470) to process the polishing surface of the polishing pad (100) while processing the polished semiconductor substrate (600).
[0190] Embodiments of the present invention
[0191] The present invention is described in detail by way of examples. The following examples are intended to further illustrate the present invention, but the scope of the examples is not limited thereto.
[0192] [Example]
[0193] raw materials
[0194] The bio-based polyols used in the following examples and comparative examples are as follows:
[0195] - ECOTRION H1000: SK Chemical, polytrimethylene ether glycol, molecular weight of 1000 g / mol, hydroxyl value of 102.0 to 124.7 mg KOH / g, and biomass content of 100 wt%.
[0196] Sovermol 1102: BASF, molecular weight 512 g / mol, hydroxyl number 230 mg KOH / g, and biomass content 80 to 100 wt%.
[0197] Priplast 1838: Croda, molecular weight 2000 g / mol, hydroxyl number 52 to 60 mg KOH / g, and biomass content 82 wt%.
[0198] Bio-based 1,3-propanediol: molecular weight of 76 g / mole, and biomass content of 100 wt%.
[0199] Example 1-1
[0200] Step 1: Preparation of bio-based urethane prepolymer
[0201] In a four-necked flask, 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-dicyclohexylmethane diisocyanate (H12MDI), 60 g of bio-based polymer polyol (ECOTRION H1000) and 5 g of diethylene glycol (DEG) were added and reacted at 80°C for 3 hours to prepare a bio-based urethane prepolymer with an NCO content of about 9 wt%.
[0202] Step 2: Preparation of the polishing layer
[0203] In a casting machine equipped with an inert gas injection line, the bio-based urethane prepolymer prepared in step 1 is loaded into a prepolymer tank, bis(4-amino-3-chlorophenyl)methane (Ishihara) is filled into a curing agent tank, and nitrogen (N2) is used as an inert gas. At the same time, 1 part by weight of a solid-phase foaming agent (AkzoNobel) and 1 part by weight of a silicon-based surfactant (Evonik) are delivered through separate pipelines to mix with the urethane prepolymer relative to 100 parts by weight of the urethane prepolymer. The raw materials are stirred while being delivered to the mixing head at a constant rate through their respective feed lines. In this case, the urethane prepolymer and the curing agent are fed at an equivalent ratio of 1:1, and nitrogen (N2) is injected as an inert gas at a rate of 0.5 to 1.5 liters / minute. The mixed raw materials are injected into a mold (1000mm×1000mm×3mm) preheated to 80°C at a filling rate of 10 kg / minute, and cast at 120°C to obtain a molded product. Thereafter, the top and bottom of the molded product were ground by 0.5 mm respectively to obtain a polishing layer (top cushion layer) having a thickness of 2 mm (specific gravity of 0.82 g / cc and an average pore diameter of 23.6 μm).
[0204] Step 3: Preparation of polishing pad
[0205] The polyester fiber nonwoven fabric was impregnated in polyurethane resin to prepare a support layer (subpad layer) with a thickness of 1.1 mm. Next, the polishing layer prepared in step 2 and the support layer were combined using a hot melt adhesive to prepare a polishing pad having a structure of a polishing layer, an adhesive layer and a support layer (thickness: 3.32 mm).
[0206] Example 1-2
[0207] In a four-necked flask, 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-dicyclohexylmethane diisocyanate (H12MDI), 50 g of bio-based polymer polyol (ECOTRION H1000) and 5 g of bio-based 1,3-propylene glycol (1.3-PDO) were added and reacted at 80°C for 3 hours to prepare a biomass-based urethane prepolymer with an NCO content of about 9 wt%.
[0208] By the same procedure as step 2 and step 3 of Example 1-1, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer, an adhesive layer and a support layer was prepared using the urethane prepolymer prepared above.
[0209] Examples 1-3
[0210] 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-dicyclohexylmethane diisocyanate (H12MDI) and 60 g of bio-based polymer polyol (Sovermol 1102) were added to a four-necked flask and reacted at 80° C. for 3 hours to prepare a biomass-based urethane prepolymer with an NCO content of about 9 wt %.
[0211] By the same procedure as step 2 and step 3 of Example 1-1, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer, an adhesive layer and a support layer was prepared using the urethane prepolymer prepared above.
[0212] Examples 1-4
[0213] In a four-necked flask, 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-dicyclohexylmethane diisocyanate (H12MDI), 50 g of bio-based polymer polyol (Priplast 1838) and 10 g of bio-based 1,3-propylene glycol (1,3-PDO) were added and reacted at 80°C for 3 hours to prepare a biomass-based urethane prepolymer with an NCO content of about 9 wt%.
[0214] By the same procedure as step 2 and step 3 of Example 1-1, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer, an adhesive layer and a support layer was prepared using the urethane prepolymer prepared above.
[0215] Comparative Example 1-1
[0216] 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-dicyclohexylmethane diisocyanate (H12MDI), 60 g of polytetramethylene ether glycol (PTMEG) and 5 g of diethylene glycol (DEG) were added to a four-necked flask and reacted at 80° C. for 3 hours to prepare a biomass-free urethane prepolymer with an NCO content of about 9%.
[0217] By the same procedure as step 2 and step 3 of Example 1-1, a polishing pad (thickness: 3.32 mm) having a structure of a polishing layer, an adhesive layer and a support layer was prepared using the urethane prepolymer prepared above.
[0218] The types and quantities of raw materials used to prepare the urethane prepolymers in the examples and comparative examples are summarized in Tables 1 and 2 below.
[0219] [Table 1]
[0220]
[0221] [Table 2]
[0222]
[0223] Test Example 1-1: Characteristics of polishing pad
[0224] (1) Hardness
[0225] Each polishing layer (thickness 2 mm, width 5 cm, and length 5 cm) and each supporting layer (thickness 1.1 mm, width 5 cm, and length 5 cm) were stored at 25°C for 12 hours, and Shore D hardness and Asker C hardness were measured using a hardness tester.
[0226] (2) Tensile strength
[0227] A tensile test was performed on each polishing layer (thickness 2 mm, length 4 cm, and width 1 cm) at a speed of 50 mm / min using a universal testing machine (UTM) to measure the maximum strength value before fracture.
[0228] (3) Elongation
[0229] A universal testing machine (UTM) was used to perform a tensile test on each polishing layer (thickness 2 mm, length 4 cm, and width 1 cm) at a speed of 50 mm / min, the maximum deformation length before fracture was measured, and the ratio of the maximum deformation length to the initial length was calculated and expressed as a percentage (%).
[0230] (4) Compressibility
[0231] Using a dial thickness gauge (Yasuda, 129-E) device, a weight of 85 g was placed on each polishing pad (thickness 3.32 mm, width 25 mm, and length 25 mm), and the thickness (A) was measured after standing for 30 seconds. Then an additional weight of 800 g was placed (the total weight was the weight of 85 g and the weight of 800 g added together), and the thickness change (B) was measured after standing for 3 minutes. The compressibility was then calculated.
[0232] Compressibility = [(A–B) / A] × 100.
[0233] The results are shown in Table 3 below.
[0234] [Table 3]
[0235]
[0236] As can be seen from the above Table 3, Examples 1-1 to 1-4 using bio-based polymer polyols generally perform well in terms of properties. In particular, in Examples 1-1 and 1-2 using bio-based polyether polyols, their properties are almost similar to those of Comparative Example 1 using petroleum-based polymer polyols, indicating that they have environmental friendliness while having physical properties comparable to those of conventional polishing pads.
[0237] Test Example 1-2: Performance of polishing pad
[0238] (1) Polishing rate (removal rate)
[0239] Each polishing pad is fixed on the pressing plate of the CMP machine, and the silicon wafer (diameter 300mm) is set in a way that its silicon oxide layer faces downward. Then the CMP process is carried out. Specifically, when the polishing load is 4.0psi, the silicon oxide layer is polished, while the pressing plate is rotated at a speed of 150rpm for 60 seconds, and the calcined cerium oxide slurry is supplied to the polishing pad at a rate of 250ml / min. After polishing, the silicon wafer is removed from the carrier, installed in a rotary dryer, cleaned with deionized water, and dried with nitrogen for 15 seconds. The thickness difference of the silicon oxide layer in the dried silicon wafer before and after polishing is measured using a spectral reflectometry thickness gauge (SI-F80R, Keyence). The polishing rate is calculated using the following equation:
[0240]
[0241] (2) Pad cutting rate
[0242] Each polishing pad was pretreated with deionized water for 10 minutes, and then conditioned for 1 hour while spraying deionized water to measure the thickness change of the polishing pad. Here, the device used for conditioning was CTS AP-300HM, and the conditioning disk used was Sasol LPX-DS2. The conditioning pressure was 6 lbf, and the rotation speed was 100 rpm to 110 rpm.
[0243] The results are shown in Table 4 below.
[0244] [Table 4]
[0245]
[0246] As can be seen from the above Table 4, Examples 1-1 to 1-4 using bio-based polymer polyols generally performed well in terms of performance. In particular, in Examples 1-1 and 1-2 using bio-based polyether polyols, the polishing rate and pad cutting rate were almost similar to those of Comparative Example 1 using petroleum-based polymer polyols, indicating that they have environmental friendliness while having comparable performance to conventional polishing pads.
[0247] Test Example 1-3: 13 C-NMR spectroscopy
[0248] For each polishing layer in the examples and comparative examples, 1 g of the polishing layer and 15 ml of a 0.3 M potassium hydroxide (KOH) aqueous solution were placed in a sealed container with a volume of 48 mL and reacted at 150° C. for 48 hours to prepare a test composition. 5 mg of the test composition was dissolved in CDCl3 and subjected to nuclear magnetic resonance (NMR) at room temperature using a JEOL 500 MHz, 90° pulse. 13 C-NMR analysis. The results are shown in Tables 5 to 7 below. In addition, peaks 1 to 3 are as shown in Figure 1 As shown, and peaks 4 and 5 are Figure 2 shown.
[0249] [Table 5]
[0250]
[0251] [Table 6]
[0252]
[0253] [Table 7]
[0254]
[0255] As can be seen from Table 7, the polishing layer prepared in some embodiments 13 Part or all of Peaks 1 to 5 were observed in the C-NMR spectrum. When the results of Test Examples 1 and 2 were analyzed together, it was confirmed that the presence of Peaks 1 to 5 was related to the characteristics and performance of the polishing pad.
[0256] Example 2-1
[0257] Step 1: Preparation of bio-based urethane prepolymer
[0258] In a four-necked flask, 35 g of toluene diisocyanate (TDI), 5 g of 4,4'-dicyclohexylmethane diisocyanate (H12MDI), 50 g of a bio-based polymer polyol (polytrimethylene ether glycol, brand name: ECOTRION H1000, manufacturer: SK Chemical, molecular weight: 1000 g / mol, hydroxyl (OH) value: 102.0 mg KOH / g to 124.7 mg KOH / g, biomass content: 100 wt%) and 5 g of bio-based 1,3-propylene glycol (molecular weight: 76 g / mol, biomass content: 100 wt%) were added and reacted at 80°C for 3 hours to prepare a bio-based urethane prepolymer having an NCO content of 8 to 12 wt%.
[0259] Step 2: Preparation of the polishing layer
[0260] In a casting machine equipped with an inert gas injection line, the bio-based urethane prepolymer prepared in step (1) was loaded into a prepolymer tank, bis(4-amino-3-chlorophenyl)methane (manufacturer: Ishihara) was filled into a curing agent tank, and nitrogen (N2) was used as an inert gas. In addition, 1 part by weight of a solid phase foaming agent (manufacturer: AkzoNobel) and 1 part by weight of a silicon-based surfactant (manufacturer: Evonik) were fed through separate lines relative to 100 parts by weight of the urethane prepolymer to be mixed with the urethane prepolymer. The raw materials were stirred while being delivered to a mixing head at a constant rate through their respective delivery lines.
[0261] In this case, the urethane prepolymer and the curing agent are fed at an equivalent ratio of 1:1, and nitrogen (N2) is injected as an inert gas at a rate of 0.5 liters / minute to 1.5 liters / minute. The mixed raw materials are discharged at a rate of 10 kg / minute, injected into a mold (length 1000 mm, width 1000 mm, and height 3 mm) preheated to 80°C, and cast at 120°C to obtain a molded product. Thereafter, the top and bottom of the molded product are ground by 0.5 mm, respectively, to obtain a polished layer with a thickness of 2 mm (specific gravity of 0.82 g / cc, and an average pore size of 23.6 μm).
[0262] Step 3: Preparation of polishing pad
[0263] The polyester fiber nonwoven fabric was impregnated with polyurethane resin to prepare a support layer (sub-pad layer) with a thickness of 1.1 mm. Then, the polishing layer prepared in step (2) and the support layer were combined using a hot melt adhesive to prepare a polishing pad having a structure of a polishing layer, an adhesive layer and a support layer (thickness: 3.32 mm).
[0264] Comparative Example 2-1
[0265] A polishing pad was prepared in the same manner as in Example 2-1, except that in step (1), ethylene glycol was used instead of bio-based 1,3-propylene glycol, and 10 g of 4,4′-dicyclohexylmethane diisocyanate (H12MDI) was used.
[0266] Comparative Example 2-2
[0267] A polishing pad was prepared in the same manner as in Example 2-1, except that in step (1), 1,4-butanediol was used instead of bio-based 1,3-propanediol, and 55 g of the bio-based polymer polyol was used.
[0268] Comparative Examples 2-3
[0269] A polishing pad was prepared in the same manner as in Example 2-1, except that in step (1), 30 g of toluene diisocyanate (TDI), 5 g of 4,4'-dicyclohexylmethane diisocyanate (H12MDI), 55 g of bio-based polymer polyol, and 5 g of 1,6-hexanediol were used.
[0270] Test Example 2-1: Hardness
[0271] The hardness of the polishing layer and the support layer of the polishing pads prepared in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, each polishing layer (thickness 2 mm, width 5 cm, and length 5 cm) and each support layer (thickness 1.1 mm, width 5 cm, and length 5 cm) were stored at 25° C. for 12 hours, and the Shore D hardness and Asker C hardness were measured using a hardness tester.
[0272] Test Example 2-2: Tensile Strength
[0273] The tensile strength of the polishing layer of the polishing pads prepared in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, a tensile test was performed on each polishing layer (thickness 2 mm, length 4 cm, and width 1 cm) at a speed of 50 mm / min using a universal testing machine (UTM), and the maximum strength value before fracture was measured.
[0274] Test Example 2-3: Elongation
[0275] The elongation of the polishing layer of the polishing pads prepared in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, a tensile test was performed on each polishing layer (thickness 2 mm, length 4 cm, and width 1 cm) at a speed of 50 mm / min using a universal testing machine (UTM), the maximum deformation length before fracture was measured, and the ratio of the maximum deformation length to the initial length was calculated and expressed as a percentage (%).
[0276] Test Example 2-4: Compressibility
[0277] The compressibility of the polishing layer of the polishing pad prepared in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, a weight of 85 g was placed on each polishing pad (thickness 3.32 mm, width 25 mm, and length 25 mm) using a dial thickness gauge (Yasuda, 129-E) device, and the thickness (A) was measured after standing for 30 seconds. Then an additional weight of 800 g (total weight of 85 g weight and 800 g weight added together) was placed, and the thickness change (B) was measured after standing for 3 minutes. The compressibility was then calculated. Compressibility = [(A–B) / A] × 100.
[0278] [Table 8]
[0279]
[0280] It can be seen from Table 8 that in the polishing pad of Example 2-1, a combination of bio-based polymer polyol and bio-based monomer polyol is used, which is not only environmentally friendly, but also has physical properties comparable to those of traditional petroleum-based polishing pads.
[0281] Test Example 2-5: Polishing Rate (Removal Rate)
[0282] The polishing pads prepared in Example 2-1 and Comparative Examples 2-1 to 2-3 were fixed on a platen of a CMP machine, and a silicon wafer (300 mm in diameter) was set with its silicon oxide layer facing downward. A CMP process was then performed to measure the polishing rate.
[0283] Specifically, the silicon oxide layer was polished under a polishing load of 4.0 psi, while the platen was rotated at a speed of 150 rpm for 60 seconds, and the calcined cerium oxide slurry was supplied to the polishing pad at a rate of 250 ml / min. After polishing, the silicon wafer was removed from the carrier, loaded into a spin dryer, rinsed with deionized water, and then dried with nitrogen for 15 seconds. The thickness difference of the silicon oxide layer in the dried silicon wafer before and after polishing was measured using a spectral reflectometry thickness gauge (model: SI-F80R, manufacturer: Keyence). The polishing rate was calculated according to the following equation:
[0284]
[0285] Test Example 2-6: Pad Cutting Rate
[0286] The pad cutting rate of the polishing layer of the polishing pads prepared in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured. Specifically, each polishing pad was pretreated with deionized water for 10 minutes and then conditioned for 1 hour while spraying deionized water to measure the thickness change of the polishing pad. Here, the device used for conditioning was CTS AP-300HM, and the conditioning disk used was Sasol LPX-DS2. The conditioning pressure was 6 lbf, and the rotation speed was 100 rpm to 110 rpm.
[0287] [Table 9]
[0288]
[0289] As can be seen from Table 9, in the polishing pad of Example 2-1, a combination of bio-based polymer polyol and bio-based monomer polyol is used, which is not only environmentally friendly, but also has physical properties comparable to those of conventional petroleum-based polishing pads. More specifically, in the polishing pad of Example 2-1, the biomass content and physical properties, such as hardness, tensile strength, and elongation, are properly controlled, so that it is not only environmentally friendly, but also has excellent performance in terms of polishing rate and pad cutting rate.
Claims
1. A polishing pad comprising a polishing layer, wherein: The polishing layer comprises a polyurethane resin, the polyurethane resin comprises a polyol and a polyisocyanate, and the polyol comprises a bio-based polymer polyol.
2. The polishing pad according to claim 1, wherein The bio-based polymer polyol has: Molecular weight of 400 g / mole to 3000 g / mole, 35mg KOH / g to 250mg KOH / g hydroxyl value, 20% to 100% by weight of biomass content, and The number of functional groups ranges from 2 to 4.
3. The polishing pad according to claim 1, wherein The bio-based polymer polyol comprises at least one selected from the following group: bio-based polyether polyol, bio-based polyester polyol, bio-based polycarbonate polyol and bio-based polycaprolactam polyol.
4. The polishing pad according to claim 1, wherein The polyurethane resin further comprises at least one bio-based monomer polyol, and a weight ratio of the bio-based polymer polyol to the bio-based monomer polyol is 5 to 20:0.01 to 2.
5. The polishing pad according to claim 4, wherein The bio-based monomer polyol comprises at least one selected from the following group: bio-based 1,3-propanediol, bio-based 1,3-butanediol, bio-based 1,4-butanediol, bio-based 2,3-butanediol, bio-based 1,5-pentanediol, bio-based 1,9-nonanediol, bio-based 1,10-decanediol and bio-based isosorbide.
6. The polishing pad according to claim 4, wherein: The bio-based monomer polyol has: 50% by weight or more biomass content, a hydroxyl value of 50 mg KOH / g to 200 mg KOH / g, and 50 g / mole to 200 g / mole weight average molecular weight.
7. The polishing pad according to claim 1, wherein: When 1 g of the polishing layer was added to a potassium hydroxide (KOH) aqueous solution having a concentration of 0.3 M, the reaction was carried out at 150° C. for 48 hours in a sealed container to obtain a test composition, and the test composition was measured. 13 C-NMR spectroscopy includes: The first peak appears between 28 ppm and 31 ppm; A second peak occurs between 31 ppm and 33 ppm; and The third peak appears between 67 ppm and 71 ppm.
8. The polishing pad according to claim 7, wherein: The ratio of the area of the first peak to the area of the second peak is 4.4 to 5.7, and the ratio of the area of the third peak to the area of the second peak is 8.2 to 8.
8.
9. The polishing pad according to claim 7, wherein: The polishing pad further includes a fourth peak appearing between 33 ppm and 36 ppm, and a fifth peak appearing between 61 ppm and 63 ppm, and a ratio of an area of the fourth peak to an area of the fifth peak is 2.1 to 6.
4.
10. The polishing pad according to claim 1, wherein: The polyisocyanate includes at least one selected from the group consisting of toluene diisocyanate (TDI), naphthalene-1,5-diisocyanate, p-phenylene diisocyanate, dimethylbiphenyl diisocyanate, 4,4-diphenylmethane diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate (H12MDI), and isophorone diisocyanate.
11. The polishing pad according to claim 1, wherein: The polishing layer has: 45Shore D to 70Shore D hardness, 15N / mm 2 Up to 27N / mm 2 The tensile strength, and 50% to 150% elongation.
12. The polishing pad according to claim 1, wherein: The polishing rate of the polishing pad in the CMP process for to And the pad cutting rate (μm / hour) is 30 μm / hour to 50 μm / hour.
13. A process for preparing a polishing pad, comprising: preparing a urethane prepolymer comprising a polyol and a polyisocyanate; and curing the urethane prepolymer to prepare a polishing layer comprising a polyurethane resin, in, The polyol comprises a bio-based polymer polyol.
14. The process for preparing a polishing pad according to claim 13, wherein: The polyols include bio-based polymer polyols and bio-based monomer polyols.
Citation Information
Patent Citations
Polishing pad with controlled crosslinking and preparation method thereof
CN112745472A
Polyurethane resin composition, film, and artificial leather
JP2021195376A
Polishing pad, process for preparing the same, and process for preparing a semiconductor device using the same
US20210129285A1
Polishing pad and method of fabricating semiconductor device using the same
US20220097197A1